Effect of HIV Housing Services on Engagement in Care and Treatment, New York City, 2011 - Terzian, Arpi S. (AIDS Behav, 2015)
The federal Housing Opportunities for Persons with AIDS (HOPWA) program addresses housing needs of low-income persons living with HIV/AIDS (PLWHA). The New York City (NYC) Department of Health and Mental Hygiene oversees 22 HOPWA contracts for over 2,400 clients, and manages the NYC HIV Registry. HOPWA clients (N = 1,357) were matched to a random 20 % sample of other PLWHA (N = 13,489). Groups were compared on HIV care retention, viral suppression, and rebound. HOPWA clients were, on average, 3 years younger and more likely to be concurrently diagnosed with HIV and AIDS. While HOPWA clients were more likely to be retained in care (94 vs. 82 %; mOR = 2.97, 95 % CI 2.35–3.74), they were no more likely to achieve suppression (84 vs. 86 %; mOR = 0.85, 95 % 0.70–1.03) and were more likely to rebound (11 vs. 7 %; mOR = 1.45; 95 % CI 1.10–1.91). HIV care retention does not fully translate to virologic suppression in this low-income service population.